Perempuan Desa dan Diversifikasi Pangan Lokal: Studi Kasus di Kabupaten Gunungkidul, DIY - Suharko, Suharko; Hudayana, Bambang (Sodality: Jurnal Sosiologi Pedesaan, 2020)
ABSTRACT This article outlines the role of rural women in diversification of local foods in Indonesia, specifically cassava. Cassava is the third main staple food in Indonesia, after rice and corn. By referring to the concept of food security and food diversification, and using the case study method, this article describes and discusses rural women’s innovations and business initiatives in developing nutritious processed cassava products in Gunungkidul Regency. These products are available at various outlets and are accessible and affordable to the public. Rural women have become the main actors in the diversification of local foods while also playing an important role in creating food security that has become a strategic agenda in Indonesia.